Shea Kernel Supply Chain and Suppliers Relationships in Rural Borgu,Niger State, Nigeria - Sidikat, Shitu; Rohaya, Mohd Nor (Interdisciplinary Research Journa, 2016)
This paper explores the roles of strong suppliers in shea kernel supply chains and the impact of their roles on the livelihood of weak suppliers (rural women) who are engaged in shea nut picking and processing. In the last few years, the media recognised that the Nigerian shea butter industry is not fully regulated, and it is confronted with a lot of sustainability challenges. While there is a call on the relevant stakeholders to take responsible action such as public enlightenment and reshaping of the supply chain network. The mechanisms that supports and create connections for actors involved in the supply chain is not very clear and as such the measures taken by the stakeholders to curb the menace seems not to hit the target. Furthermore, the negative effect of these activities on the weak suppliers seems to be greatly ignored. Therefore, studying the relationships between the strong and weak suppliers defines the specific roles of actors involved in shea kernel trade: More specifically, the local buying agents (LBAs) who create and hold the link to the broader domestic and export supply chain are studied.